Gene polymorphisms in patients with type 2 diabetes and diabetic nephropathy - Demova, Hana; Rose, Daniela; Köppel, Hannes (Central European journal of biology, 2012)
Aconsiderablevariabilityintheincidenceandprevalenceofdiabeticnephropathy(DN)cohereswithanimportantcontributionofmultigenetic predisposition in the development of DN. Some genes, which probably participate in the pathogenesis of diabetic nephropathy, also play a role in the regulation of blood pressure, familial hyperlipidemia, familial hypertension and other diseases of the cardiovascular system. We have examined the association of diabetic nephropathy, nephropathy of non-diabetic origin, hypertension and of type 2 diabetes itself with several genetic polymorphisms (the insertion/deletion polymorphism in the gene for angiotensin-converting enzyme, the G/T polymorphism in the glucose transpor ter 1 gene, the G/T (894) polymorphism and the T/C (-786) polymorphism in the eNOS gene in three groups of patients with diabetes mellitus: 1) patients without diabetic nephropathy (DM); 2) patients with DN; 3) patients with nephropathy of non-diabetic origin (NDRD). Angiotensin-converting enzyme is an important factor in a development of arterial hypertension, but in our groups of Central European diabetic patients the I/D polymorphism was not associated with diabetic nephropathy. Furthermore, we have confirmed that the T/C (T786C) polymorphism in the eNOS gene is associated with metabolic syndrome including type 2 diabetes.